The Evaluation Of The Sustainability Report Disclosure Of Brawijaya University Based On AA1000 Accountability Principles - Zuhrotul Laili; Eko Ganis Sukoharsono; Wuryan Andayani (Universitas Muhammadiyah Malang, 2025)
Purpose: To evaluate the compliance level of the sustainability report of Universitas Brawijaya period 2021-2023 based on the AA1000 Accountability Principles. Methodology/approach: Secondary data from Brawijaya University's sustainability report for the period 2021-2023 was analyzed using a content analysis approach based on the AA1000 principles. Findings: The main findings relate to the level of compliance of Universitas Brawijaya's sustainability report with the accountability principles AA1000. Practical implications: Applying the AA1000 Accountability Principles at Brawijaya University enhances the transparency and accountability of sustainability reporting. It also encourages stakeholder involvement and the development of more effective policies in sustainability reporting, thereby strengthening the university's commitment to sustainability practices. Originality/value: This research contributes new insights to the literature on sustainability disclosure in higher education, by developing an evaluation model that can be applied by other institutions. Additionally, this research highlights the relevance of the accountability principles in the local Indonesian context, showing the necessary adaptations to meet specific needs in the education sector.